AN ANALYSIS OF THE STARTUP ECOSYSTEM IN A METROPOLITAN CITY IN INDIA - Srivastava, Himanshi; Mishra, Monika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This report explores India’s dynamic urban startup ecosystem, viewing startups as drivers of innovation, resilience, and economic transformation. It traces the evolution from the 1991 economic liberalization to the present, highlighting key policy shifts, technological advancements, and globalization’s role in shaping vibrant urban hubs of entrepreneurship. Government initiatives like ‘Startup India’ are examined for their impact on fostering innovation, alongside the ecosystem’s core components—incubators, venture capital, academia, and supportive policies. The study also analyzes market trends, legal challenges (including IP and employment laws), and showcases case studies from key metropolitan cities.Concluding with future projections and policy recommendations, the report serves as a strategic guide for stakeholders, aiming to position India as a global startup powerhouse